THE EFFECT OF PEER TUTORING METHOD TOWARD LEARNING ACHIEVEMENT VIEWED FROM STUDENTS’ LEARNING MOTIVATION IN THE FORM DRAWING II SUBJECT AT DEPARTMENT OF FINE ART OF FBS UNP PADANG - Abd. Hafiz; Wisdiarman Wisdiarman (Fakultas Bahasa dan Seni UNP, 2014)
PENGARUH METODE PEER TUTORING (TUTOR SEBAYA) TERHADAP HASIL BELAJAR DITINJAU DARI MOTIVASI BELAJAR MAHASISWA DALAM MATA KULIAH MENGGAMBAR BENTUK II PADA JURUSAN SENI RUPA FBS UNP PADANGAbstractThe objective of this research was to find out the effect of Peer Tutoring Method on the students’ learning achievement with regards to their motivation in Form Drawing II class. It was a quasi-experiment research employing 2X2 factorial designs. Students at the Department of Fine Arts were the population of the research while the research samples were 60 students, from two different classes, taking Form Drawing II course during July-December 2014 academic term. The data were collected by administering questioners on motivation and administering tests to the students. A two-way variant analysis was used to analyze the data. The research findings were: 1) the students taught by using Peer Tutoring Method got better results than that of those taught by using conventional teaching methods, 2) the students having high motivation gained better achievement than those having less motivation, 3) there was no interaction between Peer Tutoring Method and student motivation on their learning results. For those reasons, lecturers teaching Form Drawing II classes and other courses with similar characteristics are suggested to use Peer Tutoring Method.Keywords: peer tutoring method, learning motivation, learning results AbstrakTujuan dari penelitian ini adalah untuk mengetahui pengaruh Metode tutor sebaya terhadap prestasi belajar siswa berkaitan dengan motivasi mereka dalam kelas Menggambar Bentuk II. Penelitian ini merupakan penelitian eksperimen semu menggunakan 2X2 desain faktorial. Mahasiswa di Jurusan Seni Rupa menjadi populasi penelitian sedangkan sampel penelitian adalah 60 mahasiswa, dari dua kelas yang berbeda, yang mengambil matakuliah Menggambar Bentuk II selama semester Juli-Desember 2014. Data dikumpulkan dengan pemberian kuesioner motivasi dan pemberian tes kepada mahasiswa. Analisis varian dua arah digunakan untuk menganalisis data. Temuan penelitian adalah: 1) mahasiswa yang diajarkan dengan menggunakan metode peer tutor mendapat hasil yang lebih baik daripada yang diajarkan dengan menggunakan metode pengajaran konvensional, 2) siswa yang memiliki motivasi tinggi memperoleh prestasi yang lebih baik daripada mereka yang memiliki motivasi kurang, 3) tidak ada interaksi antara metode totor sebaya dan motivasi siswa pada hasil belajar mereka. Untuk itu, dosen yang mengajar kelas Menggambar Bentuk II atau matakuliah lain yang memiliki karakteristik serupa disarankan untuk menggunakan metode tutor sebaya.Keywords: metode tutor sebaya, motivasi belajar, hasil belajar